Diseño de un modelo de gestión de talento humano para las pymes del cantón La Maná provincia de Cotopaxi año 2015 - Reyna Angueta, Jennifer Giulliana (2016)
Inadequate human talent management in SMEs La Mana causes a decrease in performance and profitability so many homeowners choose to close their businesses; to this problem comes the need to design of a management model Talent-oriented SMEs; for which was used, research tools such as surveys of owners was used, which allowed to know about the reality of human talent of this economic sector; among the most relevant aspects of the low level of training and inadequate recruitment and selection of staff it was evident. To achieve the goals set processes of human talent management were studied by several authors criteria using descriptive research for this purpose. By the results of the surveys the availability of the owners who felt that proper management of human talent management will contribute to the revitalization of the processes and thus increase the yield was evident.